Hypericin Enhances Paclitaxel-Induced B16-F10 Cell Apoptosis by Activating a Cytochrome c Release–Dependent Pathway - Sun, Liyun; Li, Zixuan; Shang, Huoli; Xin, Xiujuan (Frontiers in Pharmacology, 2021)
The enhanced inhibitory effect of paclitaxel (PTX) combined with hypericin (HY) on B16-F10 cells may be realized through ROS-related cytochrome c release pathway. The apoptosis characteristics of the B16-F10 cells, such as DNA fragmentation, chromatin condensation and apoptotic body formation, were all enhanced in the combined treatment group. Further studies showed that the combination of PTX and HY could increase the level of mitochondrial damage and the concentration of cytochrome c, causing the expression of caspase-3 and the cleavage of PARP increased. Compared with PTX or HY alone, the level of reactive oxygen species (ROS) increased significantly, while glutathione reductase activity (GR) and intracellular glutathione (GSH) level decreased significantly in combination group.